Contemporary fatherhood: Social, demographic and attitudinal factors associated with involved fathering and long work hours. (December 2018) - Coles, Laetitia; Hewitt, Belinda; Martin, Bill
Time pressures around work and care within families have increased over recent decades, exacerbated by an enduring male breadwinner culture in Australia and manifested in increasingly long work hours for fathers. We identified fathers who spent relatively long hours actively caring for children despite long work hours and we compared them with other fathers who did less work, less childcare, or less of both. Using 13 waves of the Household Income and Labour Dynamics in Australia (HILDA) survey, we explored characteristics associated with the time fathers spent in work and care. The age and ethnicity of fathers differentiated those who spent long hours in both work and childcare from all other groups of fathers, yet other factors were also important for the time fathers spent at work or with children. By examining fathers at the margins of the distributions of work and childcare hours, we add valuable insights into associations between work and care for families.